Trust, Performance, and Value: Predicting Student Intentions to Adopt Digital Record Applications - Gaffar, Mohammad Rizal; Pramono, Tangguh Dwi; Sutisna, Mamun; Sayuti, Abdul Malik; Setyoningrum, Ari Ani Dyah (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This study examined the factors influencing student’s intentions to adopt digital record applications in higher education, with a focus on performance expectancy, trust, effort expectancy, and perceived value. The research employed a quantitative approach, utilizing a survey of 243 undergraduate students in Bandung, Indonesia, to assess these factors. The results revealed that performance expectancy was the most significant predictor of students’ adoption intentions, confirming that students were motivated to adopt digital tools that they believe will enhance their academic performance. Trust also played a crucial role, particularly in the context of data security and privacy, which were significant concerns in educational technology adoption. Interestingly, effort expectancy, which refers to the ease of use of digital applications, did not significantly influence adoption intentions, likely due to the increasing digital literacy among students. Perceived value was found to have a positive but less pronounced effect on adoption intentions. These findings suggested that the UTAUT framework, commonly used in technology adoption studies, may need to be adapted to incorporate demographic and contextual factors, especially trust-related variables, in environments where data privacy is critical. The study also has practical implications for educational institutions and policymakers. To encourage the adoption of digital record applications, institutions should emphasize the academic performance benefits of these tools and implement trust-building strategies, such as robust data security measures.